Snap frozen! Capturing two metastable polymorphs in a tetramorphic one-dimensional coordination polymer constructed from cadmium, dithiophosphate, and 4-pyridinealdazine - Tan, Yee Seng *; Otero-de-la-Roza, Alberto; Jotani, Mukesh M.; Tiekink, Edward R. T. * (American Chemical Society, 2020)
Four polymorphs are described for the one-dimensional coordination polymer {Cd[S2P(OMe)2]2(4-pyridine-aldazine)}n (1) which features a trans-N2S4 distorted octahedral coordination geometry. Lattice energy calculations show the room temperature form, 1α, is the thermodynamically stable phase, being 1.52 kcal/mol more stable than the 1β form per unit formula. The latter is formed at 233 K on cooling 1α based on single crystal data. Single crystals of forms 1α and 1β exhibit a reversible single-crystal-single-crystal phase change which also 2 occurs in the bulk form as seen in DSC and PXRD experiments. When 1 was “snap frozen” at 100 K under a cold stream, 1β was observed most of the time but sometimes forms 1γ and 1δ were found. When warmed, 1β converted to 1α by 293 K, and each of 1γ and 1δ first converted to 1β (120-130 and 140-150 K, respectively) and then to 1α (280 K), correlating with the calculated lattice energies; subsequent cooling only yielded 1β, indicating 1γ and 1δ are metastable forms. The polymorphs exhibit different molecular packing patterns based on different non-covalent interactions and these have been evaluated by Hirshfeld surface analyses and NCI plots.